Economic Empowerment of Parents of Autistic Students at Ceria Mandiri School through Entrepreneurial Groups - Siti Fatimah Nurhayati; Muhammad Hanif Rosyidi (Urecol Journal. Part B: Economics and Business, 2022)
Economic empowerment of parents of autistic students at Ceria Mandiri school through entrepreneurship is a community service that aims to empower the economy of guardians of autistic students at Ceria Mandiri school in Cepu, Blora district, whose average economic condition is less well-off. The activities we arranged started from providing counseling, followed by creating a small food entrepreneur group with about 25 members. Production activities are carried out while they are waiting for their children and the therapist, then marketing is carried out by placing them in food stalls, canteens, cooperatives or shops, as well as minimarkets. Apart from that, the student's guardian also conducts marketing to sell it in the location around his residence. The profits are divided by way of profit sharing after deducting a portion for the foundation. So that the marketing reach can be wider, PIRT arrangements are also made to the health department. In this way, it is hoped that it can help partially ease the economic burden on parents of autistic students, especially the Ceria Mandiri school.